Genetic Variation of Nine Chicken Breeds Collected from Different Altitudes Revealed by Microsatellites - Ailin Long; Ying Qing; Ting Gu; Qing Zhu; Yiping Liu; Yan Wang; Huadong Yin; Gang Shu; Yu Zhang; Shuang Lai; Xiaoling Zhao (The Journal of Poultry Science, 2017)
Genetic polymorphisms of 19 microsatellites were investigated in nine local chicken breeds collected from low, middle and high altitudes areas in China (total number was 256) and their population genetic diversity and population structure were analyzed. All breeds were assigned into three groups, including the high (Tibetan chicken (T) and Grey chicken (G), their altitudes were above 1000 m); middle (Chengkou mountainous chicken (CK), Jiuyuan chicken (JY) and Pengxian yellow chicken (PY), their altitudes were between 500 and 1000 m), and low groups (Da ninghe chicken (DH), Tassel first chicken (TF), Gushi chicken (GS) and Wenchang chicken (WC), their altitudes were below 500 m). We found 780 genotypes and 324 alleles via the 19 microsatellites primers, and the results showed that the mean number of alleles (Na) was 17.05; the average polymorphism information content (PIC) was 0.767; the mean expected heterozygosity (He) was 0.662; as for observed heterozygosity (Ho), it was 0.647. The AMOVA results indicated the genetic variation mainly existed within individuals among populations (80%). There was no genetic variation among the three altitude groups (0%). The mean inbreeding coefficient among individuals within population (FIS) was 0.031 and the mean gene flow (Nm) was 1.790. The mean inbreeding coefficient among populations within a group (FST) was 0.157. All loci deviated Hardy-Weinberg equilibrium. The genetic distance ranged from 0.090 to 0.704. Generally, genetic variations were mainly made up of the variations among populations and within individuals. There were rich gene diversities in the populations for the detected loci. Meanwhile, frequent genes exchange existed among the populations. This can lead to extinction of the peripheral species, such as the Tibetan chicken breed.